Initial investigation on ultrasound-guided percutaneous biopsy of lesions in the first hepatic hilum with fusion of ultrasound and multimodal imaging cognitive guidance - Zeng, Xian-Tao; Liang, Xia; Hong, Zhi-Liang; Chen, Sheng; Yang, Jian-Chuan; Lin, Yu-cheng; Wu, Song-Song (Frontiers in Oncology, 2024)
Purpose This study aims to evaluate the efficacy and safety of ultrasound-guided percutaneous biopsy of the first hepatic hilum lesion, and examine its clinical value of diagnosis and treatment. Methods We conducted a retrospective study on patients diagnosed with the first hepatic hilum lesions at Fujian Provincial Hospital between February 2015 and October 2022. We selected patients who had lesions in the first hepatic hilum(including a 2cm surrounding area of the left/right hepatic ducts and upper-middle segment of the common bile duct) and the liver periphery(in the peripheral area of the liver, outside of the above-mentioned first hepatic porta region). These patients underwent percutaneous ultrasound-guided core needle biopsy (PUS-CNB) with cognitive fusion guidance using CT, MRI, or PET-CT. We compared the safety and efficacy of PUS-CNB in the first hepatic hilum and the liver periphery to explore the value of PUS-CNB in optimizing the clinical treatment of the first hepatic hilum lesions. Results The studied includes 38 cases of the first hepatic hilum cases (18 females; 20 males), 23 presented with mass-forming tumors while the remaining 15 exhibited diffuse infiltrative tumors, with an average diameter of 4.65± 2.51 cm. The percutaneous biopsy procedure, conducted under ultrasound guidance, had an average operation time of 14.55 ± 2.73 minutes, and resulted in a postoperative bleeding volume of approximately 10.79 ± 2.79 ml. The diagnostic success rate was noted to be as high as 92.11% among the participants who underwent percutaneous biopsy of the first hepatic hilum. Procedural complications, such as bleeding, bile leakage, intestinal perforation, infection or needle tract seeding, did not occur during or after the biopsy procedure. Affected by biopsy results, 5 altered their clinical treatment plans accordingly, 24patients received non-surgical treatment, 9 underwent surgical treatment, 5 underwent radiofrequency ablation for the lesions. The study comprised a total of 112 cases for percutaneous biopsy of the liver periphery. The safety and effectiveness of the two biopsy techniques were comparable, with diagnostic success rates of 92.11% VS. 94.34%, respectively (p = 0.61). Conclusion Cognitive fusion of ultrasound and multi-modal imaging for the first hepatic hilum lesion puncture biopsy is a safe and effective diagnostic procedure, with better diagnostic rate, may improve clinical value of diagnosis and treatment of various diseases.